La ejecución de los dictámenes de los comités de Naciones Unidas. El caso de España - Torrecuadrada García-Lozano, Soledad (2025)
Spain has accepted the possibility that the United Nations Committees, created in application of the human rights treaties sponsored by this International Organization, may receive individual communications in which alleged violations of the treaty text or its protocols are conveyed to them and issue their views on the matter, either confirming or denying the existence of the indicated violation. The purpose of this work is the effects of the opinions that affirm the existence of a breach by a State party within the domestic legal system, as well as the manner in which the execution of the Committee’s decision proceeds. Spanish jurisprudence has been changing, with rulings ranging from the affirmation of the insufficiency of the Committee’s opinion as a prerequisite for a review appeal, to the remittance of proceedings, including the case of CEDAW for which a particular solution was provided.